Dissociable Posterior and Anterior Insula Activations in Processing Negative Stimulus Before and After the Application of Cognitive Reappraisals - Zhang, Ze; Guo, Tingting; Fan, Jin; Wu, Xiaofei; Tan, Tengteng; Luo, Jing (Frontiers in Psychology, 2020)
Although the role of insular cortex in representing bodily and emotional feelings has been recognized, whether the posterior and anterior parts of insula play differentially in encoding and regulation of the emotional feelings is still unclear. In this function magnetic resonance imaging (fMRI) study, we examined the effect of creative cognitive reappraisals versus non-creative ordinary reappraisals on the activation pattern of the posterior and anterior insular cortex during the processing of unpleasant pictures, through comparing the neural correlates for processing these pictures before and after the application of cognitive reappraisals. We found significant anterior insular activation after the application of cognitive reappraisals especially the creative ones in contrast to the significant posterior insular activation before the application of the cognitive reappraisals. This finding supports the posterior-to-anterior progression hypothesis with the posterior insular cortex for the encoding of primary emotional feelings and the anterior insular cortex for encoding of the regulated or modulated emotional feelings.